LITERATUR REVIEW ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENGETAHUAN KARYAWAN NON MEDIS TENTANG BANTUAN HIDUP DASAR (BHD) - Fitriyanti; R.A Fadila (Jurnal Kesehatan dan Pembangunan, 2025)
Traffic accidents result in damage to several organs due to trauma. The organ that experiences damage most quickly is the brain. Accident victims' condition can get worse or lead to death if not treated quickly, especially in cases of cardiac arrest and respiratory arrest. It is very important for a nurse to learn BHD, because BHD is very necessary in emergency measures to clear the airway, assist breathing and maintain blood circulation so that it can save a person's life. The aim of the research is to analyze factors related to non-medical employees' knowledge about Basic Life Support (BHD) at the South Sumatra Province Health Office in 2024. The type of literature review used in this research is a scoping review. The keywords used in this research are factors, knowledge, non-medical employees, basic life support (BHD). It is hoped that the suggestions will provide information to the public regarding the importance of carrying out BHD. So, the public will have knowledge and insight about the factors related to Basic Life Support (BHD).